2021
DOI: 10.36740/wlek202111102
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Unhealthy Neuroticism on the Peculiarities of Personal Decision Making

Abstract: The aim: To determine the influence of unhealthy neuroticism (the high level of personal neuroticism) on the properties of the decision-making process, to identify the differences in the decision-making process features of persons with high and low levels of neuroticism. Materials and methods: A comparative design was used with two contrasting groups, which differed in the level of neuroticism. Causal relationships were defined using one-way analysis of variance (ANOVA). The methods «Diagnosis of the neurotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition to being a risk factor for many psychiatric disorders, high levels of neuroticism considerably impair the quality of daily life in people with subsyndromal levels of pathology. In the studies included in the current review, it was found that neuroticism is inversely correlated with subjective well-being, self-perceived competence, internality in interpersonal relationships, attention and memory concentration, resilience or readiness to overcome difficulties, level of personal involvement in life, and self-control in decision-making processes (Chen et al, 2023; Savchenko et al, 2021). In some studies, a higher level of neuroticism is associated with higher levels of anxiety, basic beliefs about the negative self, pessimistic expectations, and biases in interpretation (Denovan et al, 2019; Kolesnichenko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to being a risk factor for many psychiatric disorders, high levels of neuroticism considerably impair the quality of daily life in people with subsyndromal levels of pathology. In the studies included in the current review, it was found that neuroticism is inversely correlated with subjective well-being, self-perceived competence, internality in interpersonal relationships, attention and memory concentration, resilience or readiness to overcome difficulties, level of personal involvement in life, and self-control in decision-making processes (Chen et al, 2023; Savchenko et al, 2021). In some studies, a higher level of neuroticism is associated with higher levels of anxiety, basic beliefs about the negative self, pessimistic expectations, and biases in interpretation (Denovan et al, 2019; Kolesnichenko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed review of the articles included in the current analysis was conducted, in particular the studies by Savchenko et al (2021), Kolesnichenko et al (2021), Saini et al (2021), Dong et al (2022), Yang et al (2022), Tyrer et al (2022), Carvalho et al (2019), Chen et al (2023), Sarrar and Goth (2022), Weinreich Petersen et al (2022), Tonarely et al (2020), Dash et al (2019), Vigne et al (2019), and others (Cohen-Louck & Zvi, 2022; Denovan et al, 2019; Metts et al, 2021; Rachubińska et al, 2021; Rogers et al, 2021; Sewart et al, 2019; Trofimova & Sulis, 2018; Vinograd et al, 2020). The analysis confirmed that the leading personality trait of people with neurotic and neurosis-like disorders is a high level of neuroticism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroticism, openness, and consciousness personalities showed similar relationship values (confirming the first hypothesis) between PN and GC behavior, even though the explained variance was not as high as for the extraversion personality; however, PN strongly predicts GC behaviors with all f 2 values over 0.35. Environmental participation for people with neurotic personalities may be associated with worldwide inclinations to experience high levels of anxiety and emotional volatility (for example, preservation norms related to the enjoyment of our surrounding nature and the conservation of our resources) [86]. Flexible and abstract thinking, which characterizes openness, may have long-term and distant environmental effects [53].…”
Section: Discussionmentioning
confidence: 99%